L’interdiction de stade - Bérangère Ginhoux (Sociétés et Jeunesses en Difficulté)
This article deals with the stadium ban measure related to the French law for the sport events security (called Alliot Marie Law, 1993). In this article, the stadium ban will be considered as a “turning point” of the football fan’s career within a group. How this event drives him to reconsider his commitment, his memberships and his identity? This article proposes to work on the way that the Government regulates the practices of the ultra fans, by punishing some of their activities (use of pyrotechnical devices, invasion of the pitch, violence). How do the fans experience this sanction? What are the different consequences on their career? What is the particular fans’ everyday life who are stadium banned? How is this sanction collectively experienced by the ultras' group? What is its impact on the ultras’ social world? This article aims to show how, into this world, ultra fans who are stadium banned form a specific micro-world with a proper identity that is deviant labelled. The stadium ban of ultra fans, and the way they experience it, is analysed in this paper from ethnographic data of a field work, mainly realized by participant observation and semi-structured interviews with French ultra fans.